Compliance with orthokeratology care among parents of young children in Taiwan. Issue 5 (October 2021) - Chang, Li-Chun; Sun, Chi-Chin; Liao, Li-Ling
Abstract: Objectives: To evaluate compliance with orthokeratology (Ortho-K) care and its influencing factors among parents of 6–13-year-old myopic children in Taiwan. Methods: Parents who are responsible for the care of the Ortho-K lenses of their myopic children were recruited through a closed Facebook peer support group to answer an online compliance questionnaire, including the wear and care behaviours and follow-up visits of Ortho-K. Results: A total of 253 online questionnaires were analysed after excluding those with wrong information. Most participants (89.7%) were mothers and had university-level or higher education (72.3%); 67.6% of them could achieve a score equal or higher than 60% correct rate on knowledge items. In addition, 39.3% of participants had high myopia (spherical equivalent ≦ 6.0 diopters). The mean age at onset of myopia was 7.75 years for children, and 57.4% wore Ortho-K lenses for less than a year. Full compliance rate was 22.8%, as reported by fathers or mothers. The compliance rate for follow-up visits significantly increased with provision of axial length information in follow-up visits, knowledge of axial length changes as an effect of myopia control, and Ortho-K use for less than 6 months. The compliance rate for wear and care was significantly associated with high myopia in one of parents, high education level, early onset of myopia in children, knowledge of Ortho-K and myopia control, and Ortho-K use for less than 6 months. Conclusion: These results indicate the need for a comprehensive education programme for parents with young myopic children to ensure strict adherence to fitting and wear protocols and good follow-up of Ortho-K lenses.